CLASSIFICATION OF DIGITAL HEALTH TOOLS - Surin, Dmytro; Zaikina, Anna (Physical and Mathematical Education, 2023)
The paper presents a classification of digital health products by functional purpose. Formulation of the problem. The use of digital technologies in physical therapy and occupational therapy has been rapidly expanding in recent years. However, it is targeted and depends on many factors, including not only the financial aspect but also the awareness of specialists in the possibility of using digital technologies to improve their health and the health of others. Therefore, the problem of analyzing existing technologies for their practical use in physical therapy is actualized. The purpose of the study: is to classify digital health products within the framework of existing Ukrainian practices. Materials and methods. Theoretical methods of scientific knowledge were used to achieve the goal of the study: content analysis of scientific results presented in the digital scientific space and analysis of digital health tools. Results. The study made it possible to classify digital health tools according to their functional purpose: document management systems, data analytics, and forecasting systems, telerehabilitation systems, mobile application systems, mobile devices (to maintain a healthy lifestyle, to monitor blood pressure and heart rate, to control pain, to develop individual patient programs), devices, measuring devices, sensors; virtual reality (VR) and augmented reality (AR); software that comes with specialized hardware. Conclusions. The developed classification specifies the results of professional training of physical therapy specialists through the knowledge of CEP groups and the ability to use at least one representative in each of these groups in future professional activities.